2020
DOI: 10.1111/tmi.13452
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and clinical characteristics of extra‐pulmonary tuberculosis patients: a ten‐year study in the North of Iran

Abstract: Objective To determine the incidence of extra‐pulmonary tuberculosis (EPTB) and examine the risk factors and the clinical features of the disease over a ten‐year period. Methods Retrospective study of records of patients who were followed and registered in the TB registry programme in the health district of Gorgan, Iran from January 1, 2008, through December 31, 2017. Results Among 2280 TB records, 609 (26.71%) were EPTB. They were mostly female patients (53.7%) and residents in rural areas (56.5%) with a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…[ 10 ] Although the clinical symptoms were observed according to the site involved, like others, we also observed fever (97.3%) as the most common symptom, followed by loss of appetite (78.9%) and weight loss (69.1%). [ 11 , 12 ] In the present study, the maximum samples were pleural fluid (30%), followed by CSF (24.7%), ascitic fluid (16.5%), lymph node aspirate/tissue (14.7%), and pus (9.6%). Similarly, various other studies have reported pleural fluid as the most common sample received.…”
Section: Discussionmentioning
confidence: 43%
“…[ 10 ] Although the clinical symptoms were observed according to the site involved, like others, we also observed fever (97.3%) as the most common symptom, followed by loss of appetite (78.9%) and weight loss (69.1%). [ 11 , 12 ] In the present study, the maximum samples were pleural fluid (30%), followed by CSF (24.7%), ascitic fluid (16.5%), lymph node aspirate/tissue (14.7%), and pus (9.6%). Similarly, various other studies have reported pleural fluid as the most common sample received.…”
Section: Discussionmentioning
confidence: 43%
“…Since, the organ-specific symptoms are predominant and variable in each case, the constitutive symptoms are less common in EPTB. In a study from Iran, fever, fatigue, and night sweats were the most common complaints of the patients [33]. Bal et al, found that common symptoms in our country were fever, night sweats, and weight loss [30].…”
Section: Discussionmentioning
confidence: 79%
“…Osteoarticular tuberculosis is the second most common forms of extrapulmonary tuberculosis which is only less than spinal TB. 1,2,12 Hip tuberculosis (TB) is the most common osteoarticular tuberculosis, 13 consisting of 10% to 15% of total joint TB cases. Early-stage tuberculosis of the hip is often undetected due to its atypical symptoms.…”
Section: Discussionmentioning
confidence: 99%